Anticancer properties of a defensin like class IId bacteriocin Laterosporulin10 - Baindara, Piyush (Sci Rep, 2017)
Laterosporulin10 (LS10) is a defensin like peptide from Brevibacillus sp. strain SKDU10 that inhibited microbial pathogens. However, in this study, anticancer activity of LS10 was examined against different cancer cell lines and compared with normal cells. LS10 displayed cytotoxicity against cancer cells like MCF-7, HEK293T, HT1080, HeLa and H1299 at below 10 μM concentration, but not against prostate epithelium cells RWPE-1. Additionally, no hemolysis was observed at significantly higher concentration compared to IC(50) values observed for different cancer cell lines. Release of lactate dehydrogenase from cancer cell lines at 15 μM concentration upon 120 min treatment indicated the lytic ability of LS10. Accordingly, electron microscopy experiments also confirmed the necrotic effect of LS10 at 15 μM concentration against cancer cells. Furthermore, flow cytometry analysis of treated cancer cell lines revealed that LS10 induce apoptosis even at 2.5 μM concentration. Nevertheless, RWPE-1 cells remained viable even at 20 μM concentration. These results provide evidence that LS10 is an anticancer bacteriocin, which causes apoptotic and necrotic death of cancer cells at lower and higher concentrations, respectively. Taken all results together, the present study signifies that LS10 is an anticancer peptide that could be further developed for therapeutic applications.